Efficacy of Baska mask as an alternative airway device to endotracheal tube in patients undergoing laparoscopic surgeries under controlled ventilation - Pulak Tosh; Ravi B Kumar; Nishant Sahay; Saurabh Suman; Umesh K Bhadani (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Newer supraglottic devices with an additional gastric channel offer greater protection from aspiration and avoidance of laryngoscopy for their insertion would result in attenuated hemodynamic responses.The primary objective was to assess hemodynamic responses to insertion of Baska mask as compared to tracheal intubation. The time and attempts taken to secure airway and evidence of regurgitation and pulmonary aspiration of gastric contents were also assessed. Material and Methods: This prospective, randomized study was conducted in 80 patients undergoing laparoscopic cholecystectomy. All patients received standardized anaesthesia protocol. Baska mask was used to secure airway in Group B, while tracheal intubation was done in group T. Methylene blue was injected through Ryle's tube into stomach in both groups. At end of surgery, fibreoptic bronchoscopy was performed to detect bluish staining of trachea and/or main bronchi as evidence of aspiration of gastric contents and bluish staining in oropharynx as evidence of regurgitation. Chi-square test and Independent sample t-test were applied. Results: The time taken to secure airway was significantly longer in Group B as compared to Group T (45.3 ± 12.6 vs. 24.3 ± 9.1 sec) Percentage of patients who had oropharyngeal blue stain was comparable in both groups. No patient in both groups had tracheal blue stain. Group T had significantly higher HR and MAP after intubation till 10 min later. Conclusion: Baska mask insertion was associated with attenuated hemodynamic responses, though more time and attempts were required for securing the airway. It could be considered as an alternative to tracheal intubation during laparoscopic surgeries.